Pelatihan online penerapan teknologi RADIUS pada PT. Taspen (Persero) Palembang - Rahmat Novrianda Dasmen; Ade Putra; Rasmila Rasmila; Taqrim Ibadi (Universitas Hamzanwadi, 2021)
Internet network security in a company is critical. Currently, the use of wireless devices as a local data traffic controller is very widely used. However, this tool is vulnerable to network security breaches if it is not accompanied by excellent security of the network system. PT. Taspen (Persero) Palembang has problems with the Wireless network and does not have an excellent security system. It causes users who are not employees to use the internet network at the company, making employee operations slow and vulnerable to burglary. Therefore, in this PKM activity, RADIUS Technology is applied as internal network security. Every user who wants to access the internet network at the company must first log in. This activity aims to train employees of PT. Taspen (Persero) Palembang to access a wifi network that uses RADIUS Technology. It starts from accessing the wifi network, logging in, to logging out of the wifi network. This activity is carried out online by utilizing the Zoom Meeting application. The results obtained indicate that the network system security of PT. Taspen (Persero) is increasing, and all of its employees can access a wifi network that has implemented RADIUS Technology